2012
DOI: 10.1089/aid.2011.0021
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency VirusnefSignature Sequences Are Associated with Pulmonary Hypertension

Abstract: Severe pulmonary hypertension (PH) associated with vascular remodeling is a long-term complication of HIV infection (HIV-PH) affecting 1/200 infected individuals vs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 41 publications
0
46
0
2
Order By: Relevance
“…Nef is also responsible for T cell activation in infected cells [61, 62] and enhances virus production in vivo [63]. In fact, transgenic mice expressing CD4-promoter-driven Nef develop a spectrum of pathologies including AIDS-like disease [64] and vasospasm in the heart [65], and certain Nef gene variants were linked to pulmonary hypertension [66, 67]. We have recently reported that HIV-infected T cells are more potent than free virus in activating coronary arterial endothelial cells [68].…”
Section: Endothelial Dysfunction In Hiv Patientsmentioning
confidence: 99%
“…Nef is also responsible for T cell activation in infected cells [61, 62] and enhances virus production in vivo [63]. In fact, transgenic mice expressing CD4-promoter-driven Nef develop a spectrum of pathologies including AIDS-like disease [64] and vasospasm in the heart [65], and certain Nef gene variants were linked to pulmonary hypertension [66, 67]. We have recently reported that HIV-infected T cells are more potent than free virus in activating coronary arterial endothelial cells [68].…”
Section: Endothelial Dysfunction In Hiv Patientsmentioning
confidence: 99%
“…20,21 Specific nef signature sequences have been associated with PAH in 2 different HIV cohorts. 22 Bone morphogenic protein receptor 2 (BMPR-2) mutations are associated with familial PAH and result in decreased signaling through BMPR-2. 23 The HIV-1 tat (transcriptional transactivator) protein represses BMPR-2 gene expression in human macrophages in vitro, interfering with BMP–BMPR-2 transcriptional regulation.…”
Section: Pathogenesismentioning
confidence: 99%
“…Although rare, PH complicating HIV infection has not decreased appreciably with available antiretroviral therapy (ART), and the mechanistic link between PH and HIV has not been clearly established (4). Although HIV ribonucleic acid (RNA) has not been isolated in the pulmonary vasculature, HIV proteins such as Tat and Nef cause endothelial dysfunction (6)(7)(8)(9)(10)(11)(12). It stands to reason that other viral infections may cause downstream fibroproliferation and remodeling in the pulmonary circulation.…”
mentioning
confidence: 99%